Formation of MSeO4(aq) complexes (M2+ = Mg2+, Co2+, Ni2+, Cu2+, Cd2+) studied as a function of temperature by affinity capillary electrophoresis. Issue 4 (25th January 2013) - Philippini, Violaine; Aupiais, Jean; Vercouter, Thomas
<x xml:space="preserve">Abstract</x> Complexation of divalent cations (Mg2+, Co2+, Ni2+, Cu2+, Cd2+) by selenate ligand was studied by ACE (UV indirect detection) in 0.1 mol/L NaNO3 ionic strength solutions at various temperatures (15, 25, 35, 45 and 55°C). For each solution, a unique peak was observed as a result of a fast equilibrium between the free ion and the complex (labile systems). The migration time corresponding to this peak changed as a function of the solution composition, namely the free and complexed metal concentrations, according to the complexation reactions. The results confirmed the formation of a unique 1:1 complex for each cation. The thermodynamic parameters were fitted to the experimental data at 0.1 mol/L ionic strength: <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tt04nwg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(25°C) = −(6.5 ± 0.3), −(7.5 ± 0.3), −(7.7 ± 0.3), −(7.7 ± 0.3), and –(8.1 ± 0.3) kJ/mol and <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tt04nx1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> = 2.5 ± 0.2, 4.7 ± 0.4, 4.5 ± 0.6, 8.4 ± 1.1, and 7.2 ± 0.6 kJ/mol for M2+ = Mg2+, Co2+, Ni2+, Cu2+, and Cd2+, respectively. Complexes with alkaline earth and transition metal cations could be distinguished by their relative stabilities. The effect of the ionic medium was treated using the specific ion interaction theory and the thermodynamic parameters at infinite dilution were compared to previously published data on metal–selenate, metal–sulfate, and metal–chromate complexes.